Brewed for Performance: Caffeine’s Impact on Nutrition, Endurance and Strength in Sports - Michał Janiszewski; Marcin Komorowski; Rafał Kaczorowski; Jaromir Hunia; Jonasz Jurek; Alicja Kapciak; Julia Górny; Aleksandra Pelczarska; Tomasz Forenc (Journal of Education, Health and Sport)
Caffeine is one of the most widely consumed and studied stimulants worldwide with a long history in athletics as a performance enhancer. Although listed as a stimulant in the World Anti-Doping Agency’s (WADA’s) 2024 Monitoring Program, its use is not prohibited. Individual responses to caffeine vary widely due to factors like genetics, age, and lifestyle habits, such as smoking and diet.